Unusual Foreign Body of Parotid Gland Presenting as Sialolithiasis: Case Report and Literature Review - Sivapatha Sundaram Sreetharan; Rajan Philip (Case Reports in Otolaryngology)
This case report highlights an unusual case where a foreign body in the parotid gland was initially thought to be sialolithiasis based on CT scans. The foreign body was safely retrieved from the parotid gland without formal superficial parotidectomy using methylene blue and an image intensifier to localize the lesion. Diagnosis and management of foreign bodies in the parotid gland are reviewed, and surgical options in removal of such lesions are discussed.